Heavy Water Reduces GFP Expression in Prokaryotic Cell-Free Assays at the Translation Level While Stimulating Its Transcription. (25th December 2013) - Hohlefelder, Luisa S.; Stögbauer, Tobias; Opitz, Madeleine; Bayerl, Thomas M.; Rädler, Joachim O.
Abstract : The in vitro proliferation of prokaryotic and eukaryotic cells is remarkably hampered in the presence of heavy water (D2 O). Impairment of gene expression at the transcription or translation level can be the base for this effect. However, insights into the underlying mechanisms are lacking. Here, we employ a cell-free expression system for the quantitative analysis of the effect of increasing percentages of D2 O on the kinetics of in-vitro GFP expression. Experiments are designed to discriminate the rates of transcription, translation, and protein folding using pDNA and mRNA vectors, respectively. We find that D2 O significantly stimulates GFP expression at the transcription level but acts as a suppressor at translation and maturation (folding) in a linear dose-dependent manner. At a D2 O concentration of 60%, the GFP expression rate was reduced to 40% of an undisturbed sample. We observed a similar inhibition of GFP expression by D2 O in a recombinant Escherichia coli strain, although the inhibitory effect is less pronounced. These results demonstrate the suitability of cell-free systems for quantifying the impact of heavy water on gene expression and establish a platform to further assess the potential therapeutic use of heavy water as antiproliferative agent.